2014
DOI: 10.1099/ijs.0.064048-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus oriloxodontae sp. nov., isolated from the oral cavities of elephants

Abstract: Two strains were isolated from oral cavity samples of healthy elephants. The isolates were Grampositive, catalase-negative, coccus-shaped organisms that were tentatively identified as a streptococcal species based on the results of biochemical tests. Comparative 16S rRNA gene sequence analysis suggested classification of these organisms in the genus Streptococcus with Streptococcus criceti ATCC 19642 T and Streptococcus orisuis NUM 1001 T as their closest phylogenetic neighbours with 98.2 and 96.9 % gene seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that a large number of Streptococcus species colonize the oral cavities of humans and animals [2] . Among oral streptococci isolated from animals, we note: Streptococcus ursoris isolated from the oral cavities of bears [1] , Streptococcus orisratti isolated from the surface of the lower molars of Sprague-Dawley rats [3] , Streptococcus oriloxodontae isolated from the oral cavities of elephants [4] , and Streptococcus mutans isolated from dental plaque [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that a large number of Streptococcus species colonize the oral cavities of humans and animals [2] . Among oral streptococci isolated from animals, we note: Streptococcus ursoris isolated from the oral cavities of bears [1] , Streptococcus orisratti isolated from the surface of the lower molars of Sprague-Dawley rats [3] , Streptococcus oriloxodontae isolated from the oral cavities of elephants [4] , and Streptococcus mutans isolated from dental plaque [5] .…”
Section: Introductionmentioning
confidence: 99%